Accumulation o f lead and cadmium in vegetables and farmland near Hoa Khanh industrial zone, Da Nang city - Vo, Van Minh (ĐHQGHN, 2017)
Farmland around industrial zones is generally polluted by ứie emission of heavy metal from factories. Thus the farmland can potentially cause negative accumulation of heavy metal in soil and in vegetables. Hoa Khanh industrial zone where many factories are now located, has led to adverse inpacts on envừonment and habitats. The result from the scientific research has presented ứiat concenứatìon of lead in soil in Hoa Khanh Bac and Hoa Hiep Nam ward has been not yet polluted, but cadmium content is from 1.92 to 2.37 times higher than Vietnamese standard. Alternatively, heavy metal (Pb, Cd) content in spinach ự m pom ea aquaticForrsikaJ shows that it is approximately the allowed limit; concenứation of heavy metal in cabbage {Brassica junceaL. Czem. et Coss^ is over, somewhere up to 18.7 times within Pb, up to 3.4 tữnes within Cd, conpared to ứie standard. The results o f analytical coưelation between heavy metal concenừation in soil and vegetables are in a range from “weak correlation” to “sứong coưelation”. The results o f this research are expected to provide significant data for both envừonment and vegetable management aspects.